The relationship between changes in alcohol consumption and hepatic steatosis among alcohol consumers: a large-scale population-based Biobank study - Wei, Suosu; Luo, Honglin; Liu, Zhemin; Liu, Fei; Tang, Zhong; Zhu, Pinghua; Deng, Chunxia; Qu, Shenhong; Wu, Tengyan (Frontiers in Nutrition, 2025)
BackgroundThe relationship between changes in alcohol consumption and hepatic steatosis among alcohol consumers remains poorly understood. This study aimed to evaluate the association between changes in alcohol consumption and hepatic steatosis in a large population-based cohort of alcohol consumers.MethodsThis study included 33,427 participants with reported alcohol consumption, categorized as mild, moderate, or heavy at baseline and imaging visits. Hepatic steatosis was assessed via magnetic resonance (MR) imaging during the imaging visit.Results9,131 (27.3%) participants were diagnosed with hepatic steatosis at imaging visit. After adjusting for confounders, mild drinkers who progressed to moderate (aOR 1.26, 95% CI 1.10–1.44) or heavy drinking (aOR 1.70, 95% CI 1.12–2.57) had elevated odds of hepatic steatosis compared to stable mild drinkers. Moderate drinkers who maintained moderate drinking (aOR 1.36, 95% CI 1.21–1.53) or progressed to heavy drinking (aOR 2.27, 95% CI 1.84–2.79) also showed increased risk compared to those who transitioned to mild drinking. Conversely, heavy drinkers who transitioned to moderate (aOR 0.58, 95% CI 0.47–0.72) or mild drinking (aOR 0.34, 95% CI 0.25–0.45) had significantly lower odds compared to stable heavy drinkers. Stratified analyses revealed that males, individuals under 65 years, those with higher BMI, and hypertensive patients were more susceptible to hepatic steatosis with increased alcohol consumption.ConclusionIncreasing alcohol intake raises the odds of hepatic steatosis, while reducing intake lowers the odds. Public health strategies should focus on decreasing alcohol consumption to alleviate the burden of hepatic steatosis.